Economic Sanctions and International Conflicts: The Case of Russia In Comparative Perspective - Chernousov, Pavel (Université d'Ottawa / University of Ottawa, 2016)
The subject of my thesis is the following: “Economic sanctions and international conflicts: the case of Russia in comparative perspective.” I will demonstrate the impact the economic sanctions have had on a state’s foreign policy; whether they have succeeded in persuading or forcing an embargoed country to change its geopolitical actions. I believe there is a case that argues that economic sanctions can work provided that they are applied in a right manner against properly defined targets with a clear purpose. My thesis will pursue a practical aim of providing direct and proven data based on empirical analysis to reinforce the theoretical base of the tool of economic sanctions. Apart from the research conducted on past case studies, the empirical research will concentrate on the Russian case. It will make use of think-tank reports, official documents and journalists’ investigations, in which the case for sanctions with regard to Russia is well-documented. In order to understand the development of the tool of economic sanctions, this paper will also outline their main characteristics. A historical and comparative approach is best suited for this purpose, as it offers solid theoretical data to reinforce the main arguments of the study. This information provides a useful tool for building this research project in a conclusive and definitive way.
Keywords: Russia; sanctions; Ukraine